Comparing Mental Toughness In Referees and Assistant Referees In Soccer Primer League - Ismaeel, Huida; Thari, Ahmed (Journal of Physical Education, 2018)
Comparing Mental Toughness In Referees and Assistant Referees In Soccer Primer LeagueThe importance of the research lies in placing great pressure and difficult conditions on referees and assistant referees during a match or several matches. These difficulties can be objections from players, technical area objections or from the spectators at the match.